2020
DOI: 10.18599/grs.2020.1.22-31
|View full text |Cite
|
Sign up to set email alerts
|

The chemical composition and age of monazite and kularite from titanium ore of Pizhemskoye and Yarega deposits (Middle and Southern Timan)

Abstract: A study on the typomorphic characteristics and age of the monazite the two giant titanium deposits of the Timan – Pizhemskoye and Yarega, which revealed differences in morphology in the species composition of the inclusions, the grain size, distribution of chemical types of a mineral associated with conditions of crystallization and different sources of the substance. The isochronous Th-Pb monazite age was calculated using the «CHIME» method. For Yarega monazite built three isochrone with age 1301, 1105 and 77… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Several structural patterns of hexagonal rhabdophane from the Inorganic Crystal Structure Database (ICSD) and monoclinic monazite from the American Mineralogist Crystal Structure Database (AMCSD) were used as the comparison phases. The data on the orientation of the individual crystals in rhabdophane aggregates are shown as Euler color schemes, pole figures and orientation distribution density heatmaps (Mason and Schuh, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several structural patterns of hexagonal rhabdophane from the Inorganic Crystal Structure Database (ICSD) and monoclinic monazite from the American Mineralogist Crystal Structure Database (AMCSD) were used as the comparison phases. The data on the orientation of the individual crystals in rhabdophane aggregates are shown as Euler color schemes, pole figures and orientation distribution density heatmaps (Mason and Schuh, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Unfortunately, the lack of data on the space group of tristramite prevents the EBSD-based identification of this mineral. It should be noted that "kularite" (a variety of monazite) also contains Ca but by an order of magnitude less than in rhabdophane (Makeev et al, 2020).…”
Section: Chemical Composition Of Rhabdophanementioning
confidence: 99%
See 1 more Smart Citation
“…There are no zoning, quartz and carbonate veins, large segregations and crystals of ore minerals and inability of titanium transfer by hydrothermal fluid is considered a premature solution. One of the latest models suggests that the Yarega sandstones are of Neoproterozoic age, and the source of the ore material was lamprophyres for titanium phases and granites for zircon and other rare and rare earth minerals [22].…”
Section: End Of Table Hypothesis Provisions Criticismmentioning
confidence: 99%
“…Age of the Yarega deposit was erroneously taken as Middle Devonian, since the Middle Devonian pollen was found in the ore. Later it was found that the Late Devonian pollen was also present. After the formation of titaniferous sandstones of the Yarega deposit, oil migrating into them, having its own Permian-Jurassic age [21], brought the Middle-Late Devonian flora (spores and pollen) of the Devonian plants [22]. Sandy-argillaceous titaniferous rocks of the Pizhemskoye deposit do not contain leading biota.…”
mentioning
confidence: 99%